Doses de potássio em cobertura na cultura da abóbora - Sampaio Araújo, Humberto [UNESP]; de Quadros, Bárbara Rodrigues [UNESP]; Inácio Cardoso, Antonio Ismael [UNESP]; Corrêa, Carla Verônica [UNESP] (FapUNIFESP (SciELO), 2012)
Although there are recommendations for the fertilization of commercial squash crops, studies which connect the effect of topdressing potassium fertilization and yield are still rare. Thus, this study aimed at evaluating topdressing potassium doses on squash (Mirian hybrid) yield, in an experimental farm of the Universidade Estadual Paulista Júlio de Mesquita Filho, in São Manuel, São Paulo State, Brazil. The experimental design was randomized blocks, with five treatments (0.0 kg ha-1, 50.0 kg ha-1, 100.0 kg ha-1, 200.0 kg ha-1 and 400.0 kg ha-1 of K2O) and six replications. Plant growth parameters, yield and fruit quality were evaluated. After harvesting, plant (leaves + stem) and soil macronutrients were submitted to chemical analysis and data to variance and regression analysis. It was concluded that the highest yield resulted from the topdressing dose of 199.0 kg ha-1 of K2O. A reduction in calcium and magnesium contents in the plant canopy and a higher K+ content in the soil were observed for increasing K2O levels.
Topdressing potassium doses on squash crop
Keywords: Cucurbita moschata; Fruit yield; Plant nutrition